On a mild solution of a semilinear functional-differential evolution nonlocal problem. (1997) - Byszewski, Ludwik; Akca, Haydar
Abstract : The existence, uniqueness, and continuous dependence of a mild solution of a nonlocal Cauchy problem for a semilinear functional-differential evolution equation in a general Banach space are studied. Methods of a C 0 semigroup of operators and the Banach contraction theorem are applied. The result obtained herein is a generalization and continuation of those reported in references [2-8].